“Desarrollo de un sistema de costos por órdenes de producción para la carpintería Estefanía ubicada en el cantón Salcedo”. - Guatemal Llamba, Dayana Katerin (2024)
This technological proposal was proposed with the objective of improving the work order costing process in the Estefanía carpentry shop. To achieve this purpose, agile practices were implemented to facilitate the collection of information from both the beneficiaries and workers of the carpentry workshop. Through detailed interviews, we extracted the key needs and functionalities that we sought to satisfy with the development and implementation of a web application. The web application development process was carried out using modern and efficient tools. Atom was chosen as the integrated development environment (IDE), providing a flexible and powerful environment for code development. For the structure and functionality of the application, the CodeIgniter 3 framework was used, recognized for its ease of use and its ability to develop robust and scalable web applications. Regarding data management, MySQL was used as the relational database management system, ensuring an efficient and secure storage of the information required for costing and work order management. Once the application was developed, it was uploaded and deployed using the hosting service provided by Hostinger. A specific domain was assigned, which not only facilitates the identification of the page, but also helps to improve the attractiveness of the business and attract potential customers. This strategic approach to online presence will help Estefania carpentry to expand its reach and improve its competitiveness in the market.